SARS-CoV-2 seroprevalence among health care workers in a New York City hospital: A cross-sectional analysis during the COVID-19 pandemic. (January 2021) - Venugopal, Usha; Jilani, Nargis; Rabah, Sami; Shariff, Masood A; Jawed, Muzamil; Mendez Batres, Astrid; Abubacker, Muhamed; Menon, Sharika; Pillai, Anjana; Shabarek, Nehad; Kasubhai, Moiz; Dimitrov, Vihren; et al.
Highlights: SARS CoV-2 seroprevalence was high compared to the community among health care workers in the Bronx. Symptomatic participants had a higher rate of seroconversion compared to those without symptoms. Health care workers with anosmia and ageusia had higher odds of seroconversion than asymptomatic. A combination of healthcare and community exposure contributed to the seroprevalence. Abstract: Background: New York City (NYC) has endured the greatest burden of COVID-19 infections in the US. Health inequities in South Bronx predisposed this community to a large number of infectious cases, hospitalizations, and mortality. Health care workers (HCWs) are at a high risk of exposure to the infection. This study aims to assess seroprevalence and the associated characteristics of consenting HCWs from an NYC public hospital. Methods: This cross-sectional study includes serum samples for qualitative SARS-CoV-2 antibody testing with nasopharyngeal swabs for SARS-CoV-2; PCR and completion of an online survey capturing demographics, COVID-19 symptoms during the preceding months on duty, details of healthcare and community exposure, and travel history were collected from consenting participants in May 2020. Participants' risk of exposure to COVID-19 infection in the hospital and in the community was defined based on CDC guidelines. Travel history to high-risk areas was also considered an additional risk. The Odds Ratio with bivariable and multivariable logistic regression was used to assess characteristics associated with seroprevalence. Results: A total of 500 HCW were tested, 137 (27%) tested positive for the SARS-CoV-2 antibody. Symptomatic participants had a 75% rate of seroconversion compared to those without symptoms. Subjects with anosmia and ageusia had increased odds of seroconversion in comparison to those without these symptoms. Community exposure was 34% among those who had positive antibodies. Conclusion: Seroprevalence among HCWs was high compared to the community at the epicenter of the pandemic. Further studies to evaluate sustained adaptive immunity in this high-risk group will guide our response to a future surge.